A concept analysis: Support for lay healthcare workers in HIV services, Bojanala District, North West - Sarah B. Pitse; Patrone R. Risenga (AOSIS, 2023)
Background: Different lay healthcare workers play an important role in the retention of clients to human immunodeficiency virus (HIV) care. Retention to HIV care is crucial to promote treatment continuation, viral suppression and reduced risk of transmission. However, lay healthcare workers view and perceive support differently. Objectives: The aim of the study was to investigate perceptions of healthcare workers regarding support provided to lay healthcare workers in HIV services. This article is a report of a concept analysis of healthcare workers' support provided to lay healthcare workers in HIV services, that was collected during the study. A concept analysis was done to explore the support attributes, clarify meaning and to understand its use within the lay healthcare workers' context in Bojanala District, situated in the North West province of South Africa. Method: The initial phase was data collection from lay healthcare workers, their supervisors and clients on antiretroviral therapy. Thereafter, the eight concept analysis steps of Walker and Avant were followed. Peer-reviewed articles on the support concept were searched and guided by data saturation. Results: Responsiveness, provision, reciprocity and integration are key characteristics of support. Conclusion: Despite support being an interpersonal process, it is perceived subjectively. Support is necessary to continuously promote growth or endurance during adverse times. Contribution: The concept analysis will provide common understanding of support and information that is responsive to the needs of different lay healthcare workers.